The high‑resolution bathymetric dataset of the Saudi Arabian Red Sea margin from the 2022 Red Sea Decade Expedition - Marchese, Fabio; Nolan, Megan; Dunn, Natalie; Watts, Marta; von Krusenstiern, Katherine; Foy, Craig; Rodrigue, Mattie; Pieribone, Vincent; Qurban, Mohammed; Duarte, Carlos; Benzoni, Francesca (European Organization for Nuclear Research, 2026)
Gridded multibeam bathymetry of the Saudi Arabian Red Sea collected during the 2022 Red Sea Decade Expedition (funded by the National Center for Wildlife, Kingdom of Saudi Arabia). The QPS Qimera software license was provided by King Abdullah University of Science and Technology (KAUST) through baseline funding awarded to Francesca Benzoni (BAS/1/1090-01-01). The dataset includes one 40 m resolution model covering the full deep-water survey area, acquired by the Kongsberg EM 304 aboard the M/V OceanXplorer (OCX), and four 5 m resolution models of shallow-water bathymetry acquired by the Teledyne RESON SeaBat T50-P aboard Metalshark38 (MS), one per expedition Leg (L1 to L4).
Keywords: Bathymetry; High resolution; Indian ocean; License; Margin (machine learning); dept.egm

Leveraging FEMA hazard mitigation funding to preserve affordable housing in climate-vulnerable communities: a narrative policy review - Hilliman, Miracle; Egbubine, Linda; Xonu, Emmanuel; Eke-okocha, Nnaemeka; Peteranaba, Sylviastella (Journal of Environment Climate and Ecology, 2025)
Climate change is increasingly destabilizing affordable housing systems by transforming occasional disaster-related damage into a persistent driver of housing loss and displacement. Low-income households and renters are disproportionately exposed to climate-related hazards because historically affordable housing has often been developed in areas vulnerable to flooding, extreme heat, and wildfires. In the United States, the Federal Emergency Management Agency (FEMA) administers major climate adaptation initiatives through its Hazard Mitigation Assistance programs. Although these programs are primarily designed to reduce disaster risk and financial losses, their broader implications for housing affordability and community stability remain insufficiently examined. This narrative policy review synthesizes interdisciplinary research on disaster risk reduction, climate adaptation, housing affordability, and equity governance to examine how FEMA hazard mitigation funding influences affordable housing outcomes in climate-vulnerable communities. The review finds that widely used mitigation strategies, particularly property acquisition and demolition, can unintentionally reduce the supply of affordable housing and displace tenants without guaranteeing replacement housing. In contrast, in-situ mitigation and community-scale resilience measures that could preserve housing stability are less frequently implemented. Institutional barriers further complicate the integration of housing affordability goals within hazard mitigation policy. These barriers include benefit–cost analysis frameworks that undervalue social outcomes, fragmented governance between emergency management and housing institutions, and short planning horizons that overlook long-term housing impacts. By synthesizing these insights, the article reframes hazard mitigation as an investment in social infrastructure and proposes a housing-centered framework for climate adaptation policy. The findings highlight that preserving affordable housing and preventing displacement must become central objectives within hazard mitigation strategies to ensure equitable and effective climate resilience. Without housing stability, climate adaptation programs risk exacerbating the very vulnerabilities they are intended to address.
Keywords: Affordable housing; Agency (philosophy); Corporate governance; Emergency management; Equity (law); Hazard; Resilience (materials science); Subsidized housing; dept.egm

Carbon pricing and green growth: a systematic review of policy effectiveness, design, and equity - Nii-Okai, Enoch; Yeboah, Alfred; Xonu, Emmanuel; Olayode, Ayodeji; Osarodion, Efe; Wiafe, Gopal; Ackah, Albert; Enobakhare, Benjamin (Journal of Environment Climate and Ecology, 2025)
Climate change constitutes a major market failure because greenhouse gas emissions are not priced to reflect their social costs. Carbon pricing has become a central policy instrument, yet its effectiveness varies across contexts. This review evaluates the performance of carbon taxes and emissions trading systems by examining their environmental, economic, and equity outcomes. The analysis applies a systematic review framework covering peer-reviewed studies, meta-analyses, and international policy assessments published between 2008 and 2025. Evidence is synthesized across three dimensions: emissions reductions, innovation and structural change, and distributional impacts. The literature consistently shows that carbon pricing reduces emissions when price signals are strong, credible, and increase predictably over time. Jurisdictions with rising tax schedules or progressively tightening emissions caps achieve the most durable mitigation. Carbon pricing also stimulates low-carbon innovation and supports long-term structural change, especially when combined with complementary policies. Distributional outcomes vary, but equity improves significantly when revenues are returned through rebates or tax reductions. Overall effectiveness depends more on design quality and policy coherence than on whether pricing is delivered through taxes or trading systems. Credible long-term price paths, broad sectoral coverage, transparent governance, and equitable revenue use are essential conditions for achieving sustained environmental and socio-economic benefits.
Keywords: Carbon tax; Emissions trading; Equity (law); Greenhouse gas; Market failure; Revenue; Tax revenue; dept.egm

Energy burden and housing inequality: integrating environmental justice into affordable housing policy design - Hilliman, Miracle; Xonu, Emmanuel; Egbubine, Linda; Adeoba, Mariam (Journal of Environment Climate and Ecology, 2025)
Energy burden, defined as the proportion of household income spent on residential energy, represents an important yet frequently overlooked dimension of housing affordability. Conventional affordability metrics typically focus on rent or mortgage payments while neglecting the ongoing costs of energy consumption, which obscures structural forms of housing insecurity that disproportionately affect low-income and marginalized households. This paper presents a narrative review of interdisciplinary scholarship from energy policy, housing studies, urban planning, and environmental justice to examine how housing inequality functions as a systemic driver of energy burden. Drawing on the environmental justice framework of distributive, procedural, and recognitional justice, the review demonstrates that energy burden is not simply a household-level financial challenge but a structural outcome shaped by unequal housing markets, aging and inefficient housing stock, tenure insecurity, and fragmented policy governance. The synthesis also shows that existing housing and energy policies, particularly energy efficiency incentives and affordability criteria, often privilege homeowners while excluding renters, informal housing residents, and other vulnerable groups. By integrating insights from environmental justice theory with housing policy debates, this study reframes affordable housing as a critical site for addressing energy inequality. The paper concludes by proposing a novel justice-informed conceptual framework that repositions affordable housing as a primary site for energy justice intervention and provides a roadmap for more equitable housing and energy policy design.
Keywords: Affordable housing; Economic Justice; Energy poverty; Environmental justice; Incentive; Low income housing; Payment; Privilege (computing); Scholarship; dept.egm

Assessing the risk of contaminated sediments during small dam removal projects in the Long Island Sound watershed - Alix, Katelyn; Fedorchuk, Nicholas; Breslin, Vincent; Hoehne, Gary; Hayton, Jam; Balbachan, Kayla (Geological Society of America, 2025)
Keywords: Computer science; Contamination; Ecology; Environmental science; Geology; Geotechnical engineering; Hydrology (agriculture); Oceanography; Sound (geography); Watershed; dept.egm; dept.esc

Ingested Plastic in the Great Northern Diver, the Common Loon (Gavia immer) - Hilling, Thomas P.; Reynolds, Hannah T.; Breslin, Vincent T.; Pokras, Mark A. (Northeastern Naturalist, 2025)
Plastic pollution and its impact on water-reliant avifauna is a global, pervasive issue. We evaluated necropsy data of Gavia immer (Common Loon) from freshwater and marine environments in the northeastern US from 2011 to 2022, and found 16.2% (106/654) had ingested plastic items (macroplastics). We examined Common Loons stranded from 2020 to 2022, quantified macroscopic plastic items in detail, and processed the ingesta for suspected microplastics. We found macroplastics in 20.7% (11/53) and suspected microplastic particles, predominately clear fibers, in 100% (37/37) of the Common Loons. While we found no evidence that sex, mass, or geography correlated with microplastic load, both macroplastics and suspected microplastics were widespread and prevalent in Common Loon ingesta in the northeastern US. © 2025 Humboldt Field Research Institute. All rights reserved.
Keywords: dept.egm

Local scale climate change variability in New England, United States - Miller, Matthew (Climatic Change, 2025)
Keywords: Cartography; Climate change; Climatology; Ecology; Environmental science; Geography; Geology; Interpolation; Mathematics; Meteorology; New England; Oceanography; Physical geography; Precipitation; Scale (ratio); Spatial ecology; Spatial variability; Statistics; Temperature; Variation (astronomy); dept.egm; peer-reviewed

Divided by a common language? The impact of a joint international field trip on student skills - Lane, Timothy; Rourke, Maeve; Kelly, Miriah; Graves, Scott; Dalrymple, Sarah; Dick, Jonathan; Matthews, Tom; Onnis, Patrizia; Slomba, Jeff; Pétursson, Ólafur; Heidkamp, C. (Journal of Geography in Higher Education, 2025)
Fieldwork is often cited as one of the most important and effective parts of geography education, despite increasing scrutiny over its environmental and financial cost. As a result, it is imperative that any overseas fieldwork is as impactful as possible, enabling deep experiential learning. Here, we investigate the success of a joint field trip (Liverpool John Moores University, UK and Southern Connecticut State University, USA) to East Iceland. Such field trips are rare but have the potential to be extremely impactful on both cohorts of students. We outline the origins of the field trip, the considerations taken into account during planning, and the student skills we embedded into teaching. Surveys and interviews demonstrated that the field trip was highly successful, with students reporting excellent development of environmental and global awareness as well as research and leadership skills. Students also developed strong, lasting social networks, including those in the alternate university, and in Iceland. Cohorts responded similarly, suggesting that the trip presents similar opportunities to all students. We demonstrate that undertaking a joint field trip can deliver huge benefits to students, becoming a “perspective changing, and a once in a lifetime opportunity” affecting future study and career choices.
Keywords: Civil engineering; Engineering; Field (mathematics); Geography; Joint (building); Mathematics education; Pedagogy; Psychology; dept.egm; fieldwork; higher education; pedagogy; peer-reviewed; skills development

Bibliography on Land-Locked States: Fourth Revised and Enlarged Edition - Glassner, M.I. (BIBLIOGRAPHY ON LAND-LOCKED STATES: Fourth Revised and Enlarged Edition, 2023)
Keywords: dept.egm

Neptune’s domain: a political geography of the sea - Glassner, M.I. (Neptune’s Domain: A Political Geography of the Sea, 2024)
First published in 1990, Neptune’s Domain is organized around one unifying theme: the geographic aspects of the new Law of the Sea as expressed primarily in the United Nations Convention on the Law of the Sea. The first two chapters provide essential background information. Chapters 3 through 9 explain relevant provisions of the Convention. The next two chapters cover topics excluded from the Convention, and the last three chapters are more analytical and future-oriented. All students and scholars concerned with the human use of the marine environment will welcome this book, whether they be geographers, political scientists or lawyers. © Martin Ira Glassner 1990. All rights reserved.
Keywords: dept.egm

Industrial heritage in an era of climate catastrophe: Contamination as heritage - Thompson, Carolyn F. (Geographies of Post-Industrial Place, Memory, and Heritage, 2020)
The purpose of this chapter is to preliminarily explore the fruitfulness of understanding industrial heritage sites through the lens of environmental catastrophe in the 21st century. While geographers have been increasingly exploring heritage over the past few decades, concerned with its significance in terms of cultural and social representations, as well as an economic commodity, and industrial heritage has become more widely recognized as a key aspect of identity in the cities of the westernized world, research has overlooked the fascinating nexus between the industrial production marked in the sites of industrial heritage and the environmental outcomes of those processes. There is no concern more pressing in the present than the reality of climate change and environmental catastrophe and so this presentation considers exploring the interconnections between remembering the social and historical significance of industrial heritage sites and recognizing the ways these sites threaten our future. Through a preliminary case study of English Station, a disused power station on the Mill River in New Haven, Connecticut, I explore how this site represents the aspirations and progress of New Haven as an industrial, electrified, automobile city, as well as the current environmental catastrophes on our doorstep.
Keywords: dept.egm

Sustainability after COVID-19: pillars for a just transition - Morrissey, John; Heidkamp, Patrick (Environmental Sustainability, 2022)
The vulnerability of the global economy has been starkly exposed by the COVID-19 pandemic. Longer term thinking and new approaches to development and prosperity are urgently required. In this paper, we forward a series of principles on which economic and development policy for the post-COVID era should be developed. These are outlined as five ‘pillars’ from which to rebuild the global economy, based on principles of a shared sustainable prosperity. These pillars are: (I) an ecological prosperity; (II) a decarbonized economy; (III) a shared cost burden; (IV) a governance new deal; (V) a just resilience. In outlining the ‘5 pillars’ we explicitly recognize that sustainability cannot simply be a ‘green’, or environmental concern. Social and economic dimensions of sustainability are key for societal stability and continuity. This is made ever starker in the context of the fundamental economic and societal restructuring forced by the disruption of the COVID-19 pandemic. In this regard, the pillars represent a triple bottom line framing of sustainability, of mutually supportive domains of economic, social and environmental well-being. The five pillars are informed by principles of distributive and procedural justice, recognizing the importance and advantages of real community engagement and empowerment and giving due respect and deference to the ecological carrying capacity of our fragile planet. We argue that the post-COVID-19 re-build represents a once-in-a generation opportunity to markedly shift developed trajectories to more sustainable pathways, to rebalance the domains of sustainability, and in the process, to address longer-term crises including those of climate and biodiversity loss.
Keywords: COVID-19; Climate crisis; Prosperity; Resilience; Social justice; Sustainability; dept.egm; peer-reviewed

Thinking outside the ocean-climate nexus: Towards systems-informed decision making in a rapidly changing world - Germond-Duret, Celine; Germond, Basil; Katsanevakis, Stelios; Kelly, Miriah R.; Mazaris, Antonios D.; McKinley, Emma (Science of The Total Environment, 2024)
Despite repeated calls for more inclusive practices, approaches used to address current challenges within the ocean-climate nexus do not sufficiently account for the complexity of the human-social-ecological system. So far, this has prevented efficient and just decision-making and policies. We propose to shift towards systems-informed decision making, which values transdisciplinary system-thinking and cumulative impact assessments, and encourages multi-system collaboration among decision-makers in order to address the recurring technicality of policies and to foster just solutions that account for the needs of varied actors across the sustainable development spectrum.
Keywords: dept.egm; peer-reviewed

Blue Economy - Germond-duret, Celine; Garland, Michaela; Heidkamp, C. Patrick; Morrissey, John (International Encyclopedia of Geography, 2023)
Keywords: dept.egm

Breaking wind: A comparison between U.S. and European approaches in offshore wind energy leadership in the North Atlantic region - Gallaher, Adam; Graziano, Marcello; Axon, Stephen; Bertana, Amanda (Renewable and Sustainable Energy Reviews, 2023)
The United States has only recently begun investing in commercial-scale offshore wind energy (OWE). Although the United States is slow to progress, it is uniquely positioned to build on the existing knowledge that coastal European countries have applied for their own energy transitions. In this study, we analyze how federal and regional plans for expanding the OWE sector in the United States brought to the surface decade-long tensions related to multi-scale governance mismatches, jurisdictional conflicts, and unclear pathways for implementing national industrial policies. Drawing upon the European experience with OWE, we employ a dynamic multi-level perspective framework enriched by socio-ecological elements to examine the United States energy transition through its most promising technology. From our framework we identify six categories of OWE developments characterized by both unique and shared elements between the United States and European coastal countries. These elements are: (1) role of local communities, (2) governance structures, (3) multi-scale government interactions, (4) regional socioeconomic structures, (5) socio-ecological impacts, and (6) relationships with existing industries. Drawing upon our analysis, we identify and conceptually map four research areas in need of further development for the United States and the research community— (1) knowledge, (2) potential, (3) adaptation, and (4) learning. These insights provide critical information to ensure that the United States expansion into offshore energy generation is characterized by elements of justice, equity, and inclusive regional economic development.
Keywords: Blue economy; Comparative analysis; Just energy transitions; Multi-level perspective; Offshore wind energy; dept.egm; dept.soc; peer-reviewed

Introduction - Morrissey, John; Heidkamp, C. Patrick; Garland, Michaela; Krak, Louie (Demanding Sustainability: Pillars to (Re-)Build a Shared Prosperity, 2022)
This chapter introduces the 5 ‘pillars’ through which to (re-)build a shared sustainable prosperity. The five pillars aim to provide a framework through which policymakers, decision-makers, politicians, community groups and the corporate sphere might begin to consider, map out and plan for just transitions in their domains. The theoretical framing combines socio-technical transitions, social justice and just transitions perspectives; the novelty of our proposed approach here is the further inclusion of resilience perspectives, to account for the shifting relations between sustainability and resilience. Our understanding of sustainability aligns with a ‘strong sustainability’ perspective, whereby ecological limits represent ‘hard’ limits to development, limits which need to be acknowledged and respected.
Keywords: Just transitions; Pillars; Social justice; Socio-technical transitions; Strong sustainability; Sustainable prosperity; dept.egm

Shifting Sustainable Lifestyle Practices and Behaviour During Times of Pandemic Disruptive Change: Implications for on-Going Socio-Technical Transitions - Axon, Stephen; Lent, Talia; Njoku, Anuli (Energy Research & Social Science, 2023)
COVID-19 has extensively reshaped lifestyle practices, supply chain dynamics, and climate mitigation efforts. The resulting crises from the pandemic in relation to local and community sustainability practices have not yet been investigated in depth. There is a need to explore the individual characteristics and responses from rapid transitions of lifestyles at various scales. Analysing how the COVID-19 pandemic has shaped and altered sustainable living practices, and the motivations supporting them, has yet to be determined but is crucial to gain further insight to improve management responses to large-scale disruptive change. Presenting empirical findings from semi-structured interviews in New Haven County, Connecticut, this study elucidates the ways in which the lifestyles have been altered and how they responded while specifically highlighting the consequences for behavioural routines and sustainable lifestyle practices. As a result of lockdowns and pandemic mitigation responses, individual sustainability engagement fluctuated with participants shifting dietary, mobility, and energy and food consumption patterns. Specifically, participants emphasised substantial decrease in daily travel during initial phases of the pandemic alongside increased online shopping and energy use at home. Though changes to consumption practices were replaced former habits with unsustainable ones, individuals also noted how they co-opted the pandemic over time to pursue sustainable actions at home. As a macro-level ‘window of opportunity’ and disruptive change, this study illustrates how sustainable lifestyle practices were reshaped; some by choice, some by force, and some reflecting a forced choice. These findings have clear implications for the stability of maintaining sustainable practices influenced by landscape-level shocks.
Keywords: Behaviour change; COVID-19; Energy use; Food consumption; Social practices; Transport; dept.egm; dept.pch; peer-reviewed

Demanding Sustainability: Pillars to (Re-)Build a Shared Prosperity - Morrissey, John; Heidkamp, C. Patrick (Springer International Publishing, 2022)
Keywords: Climate Crisis; Covid; Covid-19; decarbonized economy; dept.egm; ecological prosperity; global economy; just resilience; resilience; social justice; sustainable governance; sustainable prosperity

Ch. 1 - Blue Economy: People and Regions in Transitions - Heidkamp, C.P.; Morrissey, J.; Germond-Duret, C.; Rourke, M. (Blue Economy: People and Regions in Transitions, 2022)
Keywords: dept.egm

Effective Stakeholder Engagement in Coastal Rransitions: Floating away from the DAD Approach towards the MOM Method - Kelly, Miriah; Axon, Stephen (Blue Economy: People and Regions in Transitions, 2022)
Emerging literature on coastal transitions in the face of the climate crisis establishes a need for identifying appropriate stakeholder engagement processes for
Keywords: dept.egm

Strengthening Industry and Academic Links Through Transdisciplinary Action Research: An Introspective Reflection of a Collaborative Water Quality, Biodiversity, and Aquaculture Initiative - Brideau, Lauren; Cross, Emma L.; Govindarajan, Annette F.; Martino, Dan; Martino, Greg; Holland, Miranda; Triay, Gabriela; Heidkamp, C. Patrick (Blue Economy: People and Regions in Transitions, 2022)
As anthropogenic impacts such as climate change ensue, coastal regions become increasingly threatened. Transdisciplinary action research (TAR) emerged as a
Keywords: SCSU-student; dept.egm

Community Acceptance of Blue Energy: Identifying Future Research Trajectories for Understanding “Place-Technology-Fit” Perceptions - Axon, Stephen (Blue Economy: People and Regions in Transitions, 2022)
Offshore renewable, or Blue Energy, installations are a crucial component of many countries’ energy policies and pathways towards a sustainable low-carbon
Keywords: dept.egm

Blue Economy: People and Regions in Transitions - Heidkamp, C. Patrick; Morrissey, John Edward; Duret, Celine Germond (Routledge, 2022)
This book presents state-of-the-art perspectives on the Blue Economy. It applies important geographical and sustainability transitions perspectives and
Keywords: dept.egm

The Evolution of Blue Carbon: Exploring the Burgeoning Role of Macroalgae in Carbon and Nitrogen Sequestration - Krak, Louie; Heidkamp, C. Patrick (Blue Economy: People and Regions in Transitions, 2022)
The recent attention on Blue Carbon (BC) signals its importance in the burgeoning Blue Economy discourse. BC has traditionally referred to carbon that is
Keywords: dept.egm

(In)justice and the blue economy - Germond-Duret, Celine; Heidkamp, C. Patrick; Morrissey, John (The Geographical Journal, 2022)
While the ocean space has long been ignored by social sciences, the past 15 years have witnessed an increased interest in the marine environment by scholars in Human Geography. The academic literature on the blue economy, almost non-existent a few years ago, is now burgeoning. The academic debate has offered some critical assessment of blue economy initiatives, but more needs to be done to address the true place of environmental protection within a blue economy, and to put people at the centre of concerns and analyses. Of particular concern, is the ambiguity of the blue economy concept and the confusion over its social and environmental sustainability, which can ultimately result in harmful practices. An important question is then how should social scientists in general and geographers, specifically, engage with these debates, and in particular how should the potential human and social costs of the blue economy be investigated and addressed while assuring justice and fairness? The papers presented here share the vision that environmental sustainability, justice and equality should be at the heart of the blue economy; not just conceptually, but practically too. The papers pursue efforts to identify blue economy risks and the mechanisms through which they occur; assess the place of inclusion and participation in a sustainable blue economy; define what blue economy policies should include to drive just and sustainable practices; and identify where the dominant understandings of the blue economy and its priorities are coming from. In other words, they put considerations of justice and broader cultural structures at the centre of their concerns and analysis. They also highlight the need to bypass geographical boundaries and gain insights from other disciplines and methodologies to grasp such an encompassing concept, and foster not just a blue economy with social justice, but a blue economy for social justice.
Keywords: blue economy; communities; dept.egm; justice; peer-reviewed; sustainability

Breaking Blue: Establishing comprehensive policy for a just and inclusive transition for the Blue Economy - Axon, Stephen; Collier, Sammy (Marine Policy, 2023)
At a time of substantial interest in the Blue Economy, it is surprising that sustainability dilemmas and justice components are not well integrated within its academic discourse or policy arena. Reviewing a number of existing U.S. coastal and marine policies, we identify that justice and equity components are essentially missing and advocate for a comprehensive policy framework for a just and inclusive transition for the Blue Economy. Looking forward, we review and critique the policy proposal of Elizabeth Warren’s Blue New Deal. While the current state of the Blue New Deal remains uncertain, we indicate that such a policy framework would integrate justice, equity and inclusivity as part of operationalising the Blue Economy. Given the proposal for a Blue New Deal is relatively new, we propose a research agenda to explore how comprehensive policy frameworks may seek to place justice and inclusivity at the centre of the Blue Economy.
Keywords: Blue Economy; Blue Justice; Blue New Deal; Governance; Sustainability; dept.egm; peer-reviewed

Geographical considerations for capturing value in the U.S. sugar kelp (Saccharina latissima) industry - Heidkamp, C. Patrick; Krak, Louie Vincent; Kelly, Miriah M. Russo; Yarish, Charles (Marine Policy, 2022)
The United States’ seaweed industry is worth over $300 million annually thanks in part to the rising popularity of seaweed-based products. Seaweed has myriad uses and great potential for novel product innovation and development while also providing numerous environmental benefits including carbon and nitrogen sequestration and other crucial ecosystem services . One of the most promising and prevalent species under domestic cultivation is Saccharina latissma. Also known as sugar kelp, this abundantly grown cold-water species dominates the edible seaweed market in the United States . This paper provides an in-depth geographical analysis of the current state of the U.S. sugar kelp industry, comparing regional market differences and opportunities for growth in Maine, Alaska, and Connecticut. Data was collected from the 2020 National Sea Grant Seaweed Symposium (https://seaweedhub.org/symposium/) and through a series of semi-structured interviews with key industry participants, yielding insights into the challenges that seaweed stakeholders face across the country. Proposed solutions for increasing the profitability of sugar kelp are explored and include market differentiation through regional origin labels, eco-labels, and quality labels.
Keywords: Eco-labels; Ecosystem services; Market differentiation; Origin labels; Quality labels; Seaweed; Sugar kelp; dept.egm; peer-reviewed

Red nectar presentation and characterization of the breeding system of an Andean nightshade - Mione, Thomas; Cotton, Anna C.; Leiva González, Segundo; Yacher, Leon I. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2022)
Flowers of Jaltomata weigendiana (Solanaceae) secrete red nectar that is visible through the partially translucent corolla. We report the pattern of nectar presentation during the sexual phases of the flower and characterize the breeding system. Comparison of flower sets experiencing daily removal starting Day 1 with flowers that accumulated nectar for one or two days prior to daily removal revealed no discernible effect on the life-of-the-flower nectar production, sugar production and floral longevity. Flowers produce about the same cumulative volume of nectar during the two sexual phases. However, cumulative nectar sugar production is about 4 times higher during the male phase. Nectar standing crop ranged from 4–26.6 µl for Day 1 flowers and 0–8.7 µl for flowers from which nectar was removed the previous day. With daily removal of nectar, 21 of 40 flowers contained no nectar during the last day of the flower’s life. All unmanipulated flowers developed fruits (autonomous self-pollination). However, manual self-pollinations and manual cross-pollinations resulted in fruits that weighed significantly more and had significantly more seeds than fruits produced by autonomous self-pollination. Protogyny and herkogamy promote cross-pollination, but delayed autonomous selfing at the end of the flower’s life ensures seed set if pollinator-mediated pollination fails.
Keywords: Autonomous self-pollination; Jaltomata; Solanaceae; colored nectar. edible fruit; dept.egm; floral longevity; peer-reviewed; protogyny; red nectar

Beyond stakeholder engagement in the coastal zone: Toward a systems integration approach to support just transformation of the blue economy - Kelly, Miriah M. Russo (The Geographical Journal, 2022)
Transformation has become a prevailing and desirable concept in blue economy literature. In parallel, researchers have been considering ways to effectively engage stakeholders to support just transformational agendas. Globally, coastal communities are already being affected by the inevitable impacts of climate change and changes to the blue economy. These pressures present complex contexts for coastal zone stakeholder engagement. In this paper, I argue that taking a systems integration approach to interacting with stakeholders is needed to support just transformational change. Assessing stakeholder systems and their relationship to coastal resources is imperative for understanding dynamics that may promote or hinder just transformation. Taking an adaptive management approach to working alongside stakeholders through transitional processes, thus building capacity, is needed to generate momentum toward just transformational change. Lastly, I explain how applications of the subsidiarity principle in integrating stakeholder systems can support a just transformational process and can inform more durable transformational outcomes.
Keywords: blue economy; coastal; dept.egm; just transition; peer-reviewed; stakeholder; systems integration; theoretical model

Tools for Healthy Living: Lessons Learned About Program Efficacy, Youth Knowledge, and Youth Engagement - Gray, Sharon; Cushman, Jennifer; Kelly, Miriah; Gaudio, Mary Margaret; Gubbins, E. Jean (The Journal of Extension, 2022)
Keywords: dept.egm; peer-reviewed

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed

Improving NGSS focused model-based learning curriculum through the examination of students’ experiences and iterated models - Park, Byung-Yeol; Campbell, Todd; Kelly, Miriah Russo; Gray, Ron; Arnold, Chester; Chadwick, Cary; Cisneros, Laura M.; Dickson, David; Moss, David M.; Rodriguez, Laura; Volin, John C.; Willig, Michael R. (Research in Science & Technological Education, 2021)
Background: It is crucial to support students in better understanding water and sustainability issues because water plays a vital role in maintaining global ecosystems, including human life. A wide range of curricular and instructional supports like those embodied in model-based learning (MBL) are necessary for teachers to engage students in the core epistemic commitments of the Next-Generation Science Standards (NGSS). Purpose: The main purpose of this study is to inform theory about students’ early attempts to engage in the complex kinds of sensemaking experiences inherent in the Framework for K-12 Science Education and the NGSS. Sample: Data for this study was collected from 74 10th grade students in a high school in the Northwest region of the New England state. Design and Methods: An explanatory sequential mixed-method research design was used to examine students’ learning outcomes, and to better understand these outcomes in connection to their experiences engaging in modeling in the MBL curriculum unit. Results: The results indicated that students’ model scores, the number of concepts in models, and the coherence and sophistication of models improved between their initial and final models. Additionally, the following patterns emerged related to ways in which students engaged in the practice of modeling: (1) students attempted to directly represent what they observed, (2) they struggled to pictorially express complex patterns or mechanisms, and (3) students experienced difficulties representing models from a diverse range of perspectives. Conclusion: The patterns identified across student models, as well as their reports of experiences related to the MBL unit implementation, provided insight into student experiences with models, while also providing meaningful implications for the refinement of the MBL curriculum unit investigated in this research specifically, while informing approaches MBL curricular units aimed at supporting NGSS implementation efforts more generally. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.egm; peer-reviewed

Who responds to health, environmental, and economic information about local food? Evidence from Connecticut seafood consumers - Tian, Yixing; Croog, Rose; Bovay, John; Concepcion, Anoushka; Getchis, Tessa; Kelly, Miriah Russo (Aquaculture Economics & Management, 2021)
We designed and implemented a discrete choice experiment to assess how information about the health, environmental, and economic benefits of locally produced aquaculture products affect Connecticut consumers’ willingness to pay (WTP) for products produced in the state, as compared with products from another state or another country. We find that information about local economic benefits tended to increase WTP for Connecticut-grown and -raised products, whereas information about health, safety, and the environment tended to decrease WTP for products from other regions. We also explore heterogeneous effects of the information treatments by respondent gender, education, and income. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.egm; peer-reviewed

Temperature-dependent effects on fecundity in a serial broadcast spawning fish after whole-life high CO2 exposure - Concannon, Callie A; Cross, Emma L.; Jones, Lucas F; Murray, Christopher S.; Matassa, Catherine M.; McBride, Richard S.; Baumann, Hannes (ICES Journal of Marine Science, 2021)
Keywords: dept.egm; peer-reviewed

Enacting a just and sustainable blue economy through transdisciplinary action research - Heidkamp, C. Patrick; Garland, Michaela; Krak, Louie (The Geographical Journal, 2021)
To enact a just and sustainable blue economy, one must consider all the actors involved in its shaping. This paper argues that a quintuple helix approach to stakeholder engagement – involving government, academia, the business community, and civil society – and an inclusive transdisciplinary action research (TAR) methodology are promising avenues with which to do so. Embracing critical pragmatism as a foundational framework, key ideas from three strands of research are consolidated: (1) the recent work on the geographical dimension of socio-technical sustainability transitions; (2) the literature on just sustainabilities and just transition; and (3) action research and transdisciplinary approaches to problem solving. This allows for the reimagination of a common future for the blue economy that is developed through a different kind of democratic process driven and informed by co-learning, and shared experiences. By adopting a transdisciplinary action research approach, actors from different disciplines and spheres of experience can gain a better mutual understanding and find commonality through the open door of collaboration. The theoretical argument presented in this paper is illustrated by a vignette of an ongoing TAR project at Southern Connecticut State University, which outlines the challenges and opportunities inherent to implementing a TAR approach. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2021 The Authors. The Geographical Journal published by John Wiley & Sons Ltd on behalf of Royal Geographical Society (with the Institute of British Geographers)
Keywords: dept.egm; peer-reviewed

Metabolic response to temperature stress in the Colombian freshwater crab Neostrengeria macropa (H. Milne Edwards, 1853) (Decapoda: Brachyura: Pseudothelphusidae) - Hudson, D.M. (Journal of Crustacean Biology, 2021)
Freshwater crustaceans are distributed throughout the montane and lowland areas of Colombia, and are therefore a useful indicator group for how aquatic species will respond to climate change. As such, metabolic determination of physiological performance was evaluated for the Colombian pseudothelphusid crab, Neostrengeria macropa (H. Milne Edwards, 1853), over a temperature range inclusive of current temperatures and those predicted by future scenarios in the plateau around the city of Bogotá, namely from 8 °C to 30 °C. The performance results mostly aligned with previous exploratory behavioral determination of the ideal temperature range in the same species, although the metabolism increased at the highest temperature treatments, a point when exploratory behavior declined. These results indicate that this species of montane crab behaviorally compensates for increased thermal stress by decreasing its physical activity, which could have negative predator-prey consequences with changes to community structure as different species undergo climate-mediated geographic range shifts in the region. As this species is endemic to the plateau surrounding Bogotá, it also experiences a number of other stressors to its survival, including infrastructure development and invasive species. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of The Crustacean Society. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: dept.egm; peer-reviewed

Assessing the resiliency of salt marshes under increasing nitrogen loading - Crosby, Sarah C.; Spiller, Nicole C.; Healy, Devan S.; Brideau, Lauren; Stewart, Luke M.; Vaudrey, Jamie M.P.; Tietz, Kasey E.; Fraboni, Peter J. (Estuaries and Coasts, 2021)
Understanding the threat to ecosystems from excess nitrogen in coastal waters is a priority issue in scientific research and natural resource management. Previous field studies have demonstrated that high nitrogen loading can decrease the health and resiliency of salt marshes through shifting biomass allocation, increasing decomposition, and causing creek bank instability, all of which can lead to increased marsh loss with sea-level rise. However, other studies have shown relatively little impact of increasing nitrogen on the structure and function of these systems. Due to the long history of eutrophication in Long Island Sound, aggressive nitrogen reduction strategies have been enacted in this region, but detrimental nutrient inputs persist at variable levels throughout the watershed. Here, the extent of nitrogen-linked salt marsh change under varying levels of nutrient stress was measured, testing the hypothesis that salt marsh resilience (as measured by Spartina alterniflora belowground biomass and marsh edge stability) decreases with increasing nitrogen loading. S. alterniflora growth (stem height, stem density, and biomass) and within-marsh creek area were quantified in 10 salt marshes along a nitrogen-loading gradient. Increasing nitrogen loading showed a significant negative relationship with dead belowground biomass in S. alterniflora; the loss of this belowground biomass in higher nitrogen systems may decrease salt marshes’ ability to keep pace with sea-level rise. Neither shifts in live biomass allocation nor a positive relationship between aboveground biomass or stem height and increasing nitrogen was observed that might promote additional sediment capture, but higher stem density could play a role in promoting sedimentation on the marsh surface in more sediment-rich systems. Aerial photography analysis revealed marsh creek expansion since 1934 at 90% of the marshes studied, but unlike findings from prior experimental enrichment studies, the rate of marsh loss did not increase with increasing nitrogen loading. Given the importance of these ecosystems and the potential of nitrogen to decrease their resiliency, understanding the impacts of eutrophication on salt marshes is critical. However, these results show that the relative importance of nitrogen in driving salt marsh loss in Long Island Sound may be less than studies from other regions have suggested. © 2021, Coastal and Estuarine Research Federation.
Keywords: Spartina alterniflora; dept.egm; peer-reviewed

Affordability, security, sustainability? Grassroots community energy visions from Liverpool, United Kingdom - Morrissey, J.; Schwaller, E.; Dickson, D.; Axon, S. (Energy Research & Social Science, 2020)
Envisioning societal futures for systemic low carbon transition is key to supporting the emergence of new configurations of the energy system. Such visions or ‘imaginaries’ facilitate wider societal support for system change. Given the urgency of the decarbonisation agenda, societal understandings of transitions processes and community ideas and visions about pathways for change assume a key role. The paper addresses an important gap in knowledge of place-based visions of energy system transition by soliciting views of community residents through a survey instrument, on what their perspectives on energy transition are. A case-study of Liverpool UK is presented, conducted as part of the EU Horizon 2020 ENTRUST project. Through a cluster analysis approach of study respondent perspectives, this study identities 4 distinct energy visions: (1) Community Affordability; (2) The Centre Ground; (3) Security First; and (4) Green Affordability. Identified visions present different perspectives on how energy is framed, with each vision characterised by distinct preferences on the extent to which stakeholder groups may influence the energy system as well as different views on the role of specific energy generation methods. Further, visions differ on the role of different actors and institutions in the energy transition. Identified energy visions provide insight into the ways in which grassroots communities consider how the energy system should transition in the coming years. The study contributes to understanding of spatially-situated and socially differentiated views of energy system transition, providing insight into contrasting viewpoints on current and future energy system priorities of residents of Liverpool, UK. © 2020 Elsevier Ltd
Keywords: Community; Energy visions; Energy-system; Grassroots; Low carbon transition; dept.egm; peer-reviewed

Contextualizing climate justice activism: Knowledge, emotions, motivations, and actions among climate strikers in six cities - Martiskainen, Mari; Axon, Stephen; Sovacool, Benjamin K.; Sareen, Siddharth; Del Rio, Dylan Furszyfer; Axon, Kayleigh (Global Environmental Change-Human and Policy Dimensions, 2020)
In August 2018, Swedish teenager Greta Thunberg started to strike from school on Fridays to protest against a lack of action on the climate crisis. Her actions sparked a historically large youth movement, leading to a series of school strikes across the world. Over the course of one week in September 2019, striking school children, students and other grassroots movements, such as Extinction Rebellion, called for everyone to participate in a global Climate Strike. This paper is based on comparative research with climate protesters in six cities: Brighton and London (United Kingdom), Montreal (Canada), New Haven and New York (USA), and Stavanger (Norway). Based on original interviews with 64 protesters, the study examines their knowledge, emotions, motivations, and actions in relation to climate change, including any lifestyle changes they have undertaken before or after their protests. Our findings show that protesters have varying degrees of knowledge about climate change, and have taken a range of actions in their own lives to address climate change. They also manifest a wide spectrum of emotions about climate change, and different motivations for taking part in climate strikes. These features are under-studied and dynamically evolving at the present conjuncture. On this basis, we call for expanded academic attention to human, emotional, epistemic, and seemingly mundane aspects of climate protests, their structural tendencies and relational expressions, and the implications for our ability to address underlying drivers. © 2020 Elsevier Ltd
Keywords: Brighton; Brighton and Hove; Canada; Climate protests; Climate strikes; Connecticut; England; Fridays for Future; Greta; Greta Thunberg; London; London [England]; Montreal; New Haven; New York; Norway; Quebec [Canada]; Rogaland; Social activism; Social movements; Stavanger; United Kingdom; United States; action plan; climate change; dept.egm; environmental justice; knowledge; lifestyle; peer; peer-reviewed; psychology

The socio-cultural dimensions of community-based sustainability: Implications for transformational change - Axon, Stephen (Journal of Cleaner Production, 2020)
There is substantial difficulty with effectively, and meaningfully, engaging the public with community-based sustainability projects as a method to facilitate sustainable lifestyles. Individuals engage with community projects in numerous ways: cognitively (knowledge), affectively (emotions), and behaviourally (actions). One prevalent consideration that individuals consider is other peoples’ (lack of) engagement; given that the success of community-based approaches addressing climate change is dependent upon the actions, and participation, of all local residents. Findings from focus groups in seven urban communities in the UK are presented that illustrate clear elements of ‘Othering’ as part of individual engagements with community-based sustainability projects. Primarily, there is substantial consideration towards what other people within the community know, feel, and do to engage with community-based projects. Residents distinguish themselves in opposition to those they view as engaging, and not engaging, in the same way as themselves and indicate the need for equitable participation amongst all residents. These considerations have the potential to project particular barriers on wider community engagement if left to develop, cause tension, and are not resolved. Implications for participatory strategies to meaningfully and effectively engage individuals with community-based sustainability and transformational change are outlined. Insights into how considerations of ‘Othering’ can be overcome so as not to cause negative engagements with other residents and attempts to live sustainably as part of a community approach are illustrated. © 2020
Keywords: Climate change; Communities; Community based approach; Community engagement; Community project; Community-based; Community-based projects; Local residents; Othering; Public engagement; Sustainability project; Sustainability science; Sustainable development; Sustainable lifestyles; Transformational change; Transformations; Urban community; dept.egm; peer-reviewed

Just energy transitions? Social inequities, vulnerabilities and unintended consequences - Axon, Stephen; Morrissey, John (Buildings and Cities, 2020)
Keywords: dept.egm; peer-reviewed

“I’m a bit of a waster”: Identifying the enablers of, and barriers to, sustainable food waste practices - Wakefield, Alysia; Axon, Stephen (Journal of Cleaner Production, 2020)
Food waste has become an area of increasing concern in recent years, since unsustainable food waste practices have been associated with a range of adverse environmental, economic and societal impacts. Food waste is a multi-sectoral issue and must be addressed as such, by ensuring policymakers, practitioners, and consumers are equipped with the relevant knowledge and understanding of the importance of sustainable food waste practices. By exploring current attitudes and understanding of this topic amongst consumers, a lack of education about the importance of this issue has been identified as a barrier to carrying out sustainable practices at the household level, along with excess packaging, cultural norms of overconsumption and inappropriate social marketing. In contrast, a number of enablers, including social pressures, access to appropriate facilities and encouragement from media advertisements appear to have been highly influential in infringing on the consciousness of consumers. Investigating these enablers and barriers has allowed a number of potential interventions to be identified, with the intention of addressing this issue using a multifaceted approach and encouraging society to carry out sustainable food waste practices in the future. © 2020
Keywords: Contrast media; Cultural norms; Economic and social effects; Food waste; Food waste management; Household level; Marketing; Multi-faceted approach; Policy makers; Social marketings; Social pressures; Societal impacts; Sustainable consumption; Sustainable development; Sustainable lifestyles; Sustainable practices; dept.egm; peer-reviewed